Roles and Responsibilities of Notary in Making the Results Agreement of Criminal Sanctions - Husni Basya; Dwi Kurniawan; Sri Endah Wahyuningsih (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Notary institutions emerge from the growing needs of society today. Which requires evidence of the relationship existing civil law and / or between them, the general rule as to where and when the law demands it or it is desired by the community, to make written evidence that has authentic power. On 16 June 1925, out instructions to the Notary who practice in Indonesia, instruction, which contains 10 articles containing provisions that a Public notary before the first practice was sworn in. Notary Oath become a necessity of Principles of Public Law (Publiek Rechtelijk Beginsel):